Thermal Expansion, Heat Capacity, and Thermal Conductivity of Nickel Ferrite (NiFe2O4). Issue 5 (1st April 2014) - Nelson, Andrew T.; White, Joshua T.; Andersson, David A.; Aguiar, Jeffery A.; McClellan, Kenneth J.; Byler, Darrin D.; Short, Michael P.; Stanek, Christopher R.; White, M.
<x xml:space="preserve">Abstract</x> Nickel ferrite (NiFe2O4) is a major constituent of the corrosion deposits formed on the exterior of nuclear fuel cladding tubes during operation. NiFe2O4 has attracted much recent interest, mainly due to the impact of these deposits, known as CRUD, on the operation of commercial nuclear reactors. Although advances have been made in modeling CRUD nucleation and growth under a wide range of conditions, the thermophysical properties of NiFe2O4 at high temperatures have only been approximated, thereby limiting the accuracy of such models. In this study, samples of NiFe2O4 were synthesized to provide the thermal diffusivity, specific heat capacity, and thermal expansion data from room temperature to 1300 K. These results were then used to determine thermal conductivity. Numerical fits are provided to facilitate ongoing modeling efforts. The Curie temperature determined through these measurements was in slight disagreement with literature values. Transmission electron microscopy investigation of multiple NiFe2O4 samples revealed that minor nonstoichiometry was likely responsible for variations in the Curie temperature. However, these small changes in composition did not impact the thermal conductivity of NiFe2O4, and thus are not expected to play a large role in governing reactor performance.